2017
DOI: 10.1111/vsu.12705
|View full text |Cite
|
Sign up to set email alerts
|

A Carrel patch technique for renal transplantation in cats

Abstract: The Carrel patch is a novel approach allowing the harvest of kidneys with multiple renal arteries. The technique also simplified the implant procedure, potentially decreasing the risks of bleeding and thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This modification allowed us to maximize the length of vessels and avoid damage to the graft artery. Budgeon et al reported that a carrel patch technique could reduce the risk of thrombosis and leakage by displacing the suture line away from the entrance to the renal artery (19). Carrel et al and Mazzucchi et al.…”
Section: Discussionmentioning
confidence: 99%
“…This modification allowed us to maximize the length of vessels and avoid damage to the graft artery. Budgeon et al reported that a carrel patch technique could reduce the risk of thrombosis and leakage by displacing the suture line away from the entrance to the renal artery (19). Carrel et al and Mazzucchi et al.…”
Section: Discussionmentioning
confidence: 99%
“…The graft's main renal artery is anastomosed to the recipient's external or internal iliac artery in end-to-side or end-toend anastomosis, respectively. With multiple donor renal arteries, an aortic patch ("Carrell patch"-containing the multiple renal arteries) is used to anastomose to the recipient's external iliac artery [13]. The main renal vein is anastomosed to the recipient's external or internal iliac vein.…”
Section: Introductionmentioning
confidence: 99%